Fullerene modified copper-containing mixed metal silicon oxide catalyst as well as preparation method and application thereof
By developing a fullerene-modified copper-containing mixed metal silicon oxygen catalyst, the problems of harsh reaction conditions and poor catalyst performance in the preparation of 1,3-propylene glycol were solved, and the preparation of 1,3-propylene glycol was achieved with high efficiency and good selectivity.
Patent Information
- Application Number
- CN202311394433.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, the reaction conditions during the preparation of 1,3-propylene glycol are harsh and the catalyst performance is poor, resulting in insufficient conversion and selectivity, making it difficult to achieve industrial production.
A fullerene-modified copper-containing mixed metal silicon oxygen catalyst was developed to form a catalyst system with high catalytic activity by combining fullerene, copper salt and transition metal salt with silicon oxygen. The catalyst stabilizes the presence of Cu+ and improves catalytic performance through calcination and reduction treatment.
Under mild conditions, the catalyst can significantly increase the conversion rate of 3-hydroxypropionate and the selectivity of 1,3-propanediol, reaching more than 99.3% and 98.2%, solving the problems of harsh reaction conditions and poor catalyst performance in the prior art.
Smart Images

Figure BDA0004513395220000141 
Figure BDA0004513395220000161 
Figure BDA0004513395220000171
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and preparation of 1,3-propylene glycol, and specifically relates to a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst and a preparation method and application thereof. Background Art
[0002] 1,3-propylene glycol is an antifreeze agent and a raw material for the synthesis of various plasticizers, detergents, preservatives and emulsifiers. The more important application of 1,3-propylene glycol is as a polymerization monomer. 1,3-propylene glycol and terephthalic acid undergo polymerization to form polytrimethylene terephthalate (PTT), a new type of polyester material that can be used to make fiber yarns, produce high-quality carpets and other fabrics, and can also be used in plastic products. In this field, a more interesting research is to invent a preparation route for 1,3-propylene glycol that is both economical and effective and has process advantages.
[0003] The main synthetic routes of 1,3-propylene glycol include acrolein water and hydrogenation, microbial fermentation, 1,3-dichloropropane hydrolysis and ethylene oxide carbonylation. Among them, the ethylene oxide carbonylation process is divided into two routes: one is that ethylene oxide is hydroformylated to generate 3-hydroxypropanal and then hydrogenated to form 1,3-propylene glycol; the other is that ethylene oxide is hydromethylated to generate 3-hydroxypropionic acid methyl ester and then hydrogenated to form 1,3-propylene glycol. The intermediate product of the first route is unstable, and the intermediate product of the second route is stable but the hydrogenation conditions are harsh. Therefore, the development of an efficient hydrogenation catalyst suitable for mild reaction conditions is crucial for energy saving and consumption reduction.
[0004] In 1996, Shell Company of the United States claimed to have achieved the industrial production of 1,3-propylene glycol. The company's patent described the method of preparing 1,3-propylene glycol by hydroformylation in one step using ethylene oxide, CO and H2 as raw materials (US3463819). In 2001, Shell Company conducted a study on the hydrogenation of 3-hydroxypropionate. Patent US6191321B1 showed that at a liquid hourly space velocity of 1h -1, pressure 1500psig, temperature 165 ~ 190 ℃, using Cu-ZnO catalyst and Cu-ZnO catalyst doped with Zr and Ba, the conversion rate is between 50.2 ~ 99.6%, and the selectivity of 1,3-propylene glycol is 40.3 ~ 60.7%. Samsung Electronics also applied for a patent for copper chromate or Pd / C catalyst, but the catalytic performance is poor. At 1500psig, 180℃, 15h, the conversion rate of 3-hydroxypropionate is 5%, and the selectivity of 1,3-propylene glycol is only 3% (US6348632B1 and US6521801B2). Subsequently, in its patent request in 2002 (CN1355160A), it used Cu-Si-O as the main catalyst and added a small amount of Re, Pd, Ru, Pt, Rh, Ag, Se, Te, Mo, and Mn as auxiliary agents. The examples show that at 145-150°C and 62-69 bar pressure, the conversion rate of methyl 3-hydroxypropionate is 82.9-97.9%, and the selectivity of 1,3-propylene glycol can reach 84.3-89.6%. In 2007, the patent CN101020635A of Lanzhou Institute of Chemical Physics disclosed that Cu / TiO2-SiO2 catalyst can catalyze the conversion rate of methyl 3-hydroxypropionate to 80.3-93.9% at 140°C and 7MPa, and the selectivity of 1,3-propylene glycol is 79.6-88.2%. In 2019, the patent CN110105169A of Xiamen University disclosed that Mn 0.15 Cu 1.8 SiO 3.5 The catalyst can catalyze the conversion rate of methyl 3-hydroxypropionate to 94.0% and the selectivity of 1,3-propylene glycol to 85.4% at 160°C and 64atm.
[0005] At present, research in this field shows that the preparation of 1,3-propylene glycol by hydromethylation-hydrogenation of ethylene oxide has not yet been achieved in industrial production, and the reaction conditions involved in the current research on catalysts are harsh. Therefore, the invention of a reasonable and efficient catalyst system and the design of a cost-effective and process-advantageous preparation route for 1,3-propylene glycol are key points. Summary of the invention
[0006] In view of the existing situation, the present invention provides a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst and a preparation method and application thereof.
[0007] In order to solve the above technical problems, the present invention provides a catalyst in the first aspect, wherein the general formula of the catalyst is C' x M y Cu z / (SiO2) m; wherein C' is selected from fullerene C60 or C70; M is selected from at least one of transition metal elements and / or lanthanide metal elements; 0.05≤x≤0.39, 0.01≤y≤0.20, 0.20≤z≤0.50, 0.40≤m≤0.74, and x+y+z+m=1; preferably 0.1≤x≤0.2, 0.04≤y≤0.1, 0.1≤z≤0.2, 0.55≤m≤0.7, and x+y+z+m=1.
[0008] According to some embodiments of the present invention, M is selected from any one, any two, or any three of zinc, manganese, zirconium, titanium, chromium, cobalt, silver, gold, lanthanum, cerium, praseodymium, and europium.
[0009] The second aspect of the present invention provides a method for preparing the above catalyst, comprising the following steps: mixing fullerene, copper salt, M salt and a carrier, adding an alkaline precipitant, reacting to obtain a precursor, and calcining the precursor under an inert atmosphere.
[0010] According to some embodiments of the present invention, the mass ratio of the fullerene, copper salt, M salt, carrier and alkaline precipitant is 2.0:(5-20):(1-15):(15-50):(1-50), preferably 2.0:(7.6-15.1):(2.3-9.2):(18.3-47):30.
[0011] According to some embodiments of the present invention, the alkaline precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, urea, ammonia water, ammonium carbonate, ammonium bicarbonate, sodium methoxide, sodium ethoxide, sodium n-propoxide, potassium methoxide, potassium ethoxide, potassium n-propoxide, potassium isopropoxide, potassium n-butoxide, potassium isobutoxide, potassium tert-butoxide, sodium amide, and potassium amide.
[0012] According to some embodiments of the present invention, the preparation method further comprises: drying the precursor before calcining; preferably, the drying temperature is 50°C to 150°C, more preferably 90°C to 120°C, for example 120°C, and the drying time is 6 hours to 15 hours, more preferably 10 hours to 12 hours, for example 12h.
[0013] According to some embodiments of the present invention, the calcination temperature is 200°C to 600°C, preferably 300°C to 400°C, such as 400°C, and the calcination time is 2 hours to 8 hours, preferably 4 hours to 6 hours, such as 6 hours.
[0014] According to some embodiments of the invention, the inert atmosphere is nitrogen.
[0015] According to some embodiments of the present invention, the copper salt is selected from at least one of copper sulfate, copper nitrate, cuprous sulfate, organic acid copper, copper halide, cuprous halide, cuprous nitrate, and organic acid cuprous;
[0016] And / or, the fullerene is selected from C60 or C70;
[0017] And / or, the M salt is selected from ruthenium acetate, nickel sulfate, nickel nitrate, nickel acetate, cobalt sulfate, cobalt nitrate, cobalt acetate, ferric sulfate, ferric nitrate, ferric acetate, silver sulfate, silver nitrate, silver acetate, rhodium nitrate, chloroauric acid, zinc sulfate, zinc nitrate, zinc chloride, zinc acetate, manganese sulfate, manganese nitrate, manganese acetate, chromium sulfate, chromium nitrate, chromium acetate, lanthanum nitrate, lanthanum acetate, cerium nitrate, cerium acetate, praseodymium sulfate, praseodymium nitrate, acetic acid At least one of praseodymium, neodymium sulfate, neodymium nitrate, neodymium acetate, samarium sulfate, samarium nitrate, samarium acetate, europium sulfate, europium nitrate, europium acetate, gadolinium sulfate, gadolinium nitrate, gadolinium acetate, dysprosium sulfate, dysprosium nitrate, dysprosium acetate, holmium sulfate, holmium nitrate, holmium acetate, erbium sulfate, erbium nitrate, erbium acetate, thulium sulfate, thulium nitrate, thulium acetate, ytterbium acetate, cadmium acetate, cadmium sulfate, cadmium nitrate, zirconium sulfate, zirconium nitrate, zirconium acetate, and hafnium sulfate;
[0018] And / or, the carrier is a silica sol solution, and the mass fraction concentration of the silica sol solution is 5% to 40%, preferably 10% to 30%, for example 30%.
[0019] According to some embodiments of the present invention, the preparation method further includes: a step of heating and aging the precursor before drying, preferably, the heating temperature is 50°C to 100°C, and the aging time is 4h to 16h; more preferably, the heating temperature is 60°C to 90°C, for example 90°C, and the aging time is 8h to 12h, for example 12h.
[0020] According to some embodiments of the present invention, the preparation method further comprises the steps of collecting the precipitate by filtration after heating and aging, and washing the precipitate with deionized water.
[0021] According to some embodiments of the present invention, the preparation method further includes: a reduction step of the precursor after calcination; preferably, the reduction is carried out using a reducing gas, and the flow rate of the reducing gas is 90 mL / min; more preferably, the reducing gas is hydrogen or a mixture of hydrogen and nitrogen; further preferably, the reduction temperature is 250°C to 500°C, and further preferably 250°C to 450°C, for example 400°C, and the reduction time is 3 hours to 8 hours, and further preferably 4 hours to 5 hours, for example 4 hours and 40 minutes.
[0022] The third aspect of the present invention provides a method for preparing 1,3-propylene glycol. In the presence of the above catalyst or the catalyst prepared by the above preparation method, 3-hydroxypropionic acid ester is contacted with hydrogen to react to prepare 1,3-propylene glycol.
[0023] According to some embodiments of the present invention, the molar ratio of the 3-hydroxypropionic acid ester to hydrogen is 1:(100-1000), for example 1:100; and / or the 3-hydroxypropionic acid ester is selected from one of methyl 3-hydroxypropionate, ethyl 3-hydroxypropionate, propyl 3-hydroxypropionate, butyl 3-hydroxypropionate, and pentyl 3-hydroxypropionate.
[0024] According to some embodiments of the present invention, the contact reaction is carried out in the presence of a solvent; preferably, the volume ratio of the 3-hydroxypropionic acid ester to the solvent is 1:(8-10), for example 1:8; and / or the solvent is selected from any one of alcohols, ethers, saturated alkanes, and saturated aromatic hydrocarbons, more preferably, the alcohol is selected from any one of methanol, ethanol, propanol, and butanol, the ether is selected from any one of diethyl ether, methyl tert-butyl ether, and tetrahydrofuran, and the saturated alkane is selected from any one of hexane, heptane, and octane.
[0025] According to some embodiments of the present invention, the conditions of the contact reaction include a reaction temperature of 80°C to 220°C, preferably 100°C to 180°C, such as 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C; a reaction pressure of 1atm to 40atm, preferably 1atm to 10atm, such as 1atm, 2atm, 4atm, 6atm, 8atm, 10atm; a reaction time of 0.1 hour to 500 hours; a liquid hourly volume space velocity of 0.02h -1 ~1.0h -1 , preferably 0.2h -1 ~0.8h -1 , for example 0.3h -1 .
[0026] According to some embodiments of the present invention, during the contact reaction, the flow rate of 3-hydroxypropionate is 0.02 mL / min to 0.20 mL / min, for example, 0.02 mL / min, 0.04 mL / min, 0.06 mL / min,
[0027] The flow rate of hydrogen is 30mL / min to 100mL / min, for example, 30mL / min, 35mL / min, 40mL / min, 45mL / min, 50mL / min, 60mL / min, 70mL / min, 80mL / min, 90mL / min, 100mL / min.
[0028] Beneficial effects:
[0029] The catalyst prepared by the preparation method of the present invention can make full use of the "electronic buffer" mechanism of fullerene, so that fullerene and Cu interact with each other electronically to protect the unstable Cu + Protected from oxidation and reduction, and maintain catalytically active Cu0 / Cu + ratio; this method stabilizes the active species Cu during the catalytic reaction + The presence of significantly improves the catalytic activity and catalyst life of the copper-containing mixed metal silicon-oxygen catalyst;
[0030] When the catalyst of the present invention is used to hydrogenate 3-hydroxypropionic acid ester to prepare 1,3-propylene glycol, the reaction temperature is 100°C to 180°C, the reaction pressure of hydrogen is 1atm to 40atm, the hydrogen-ester ratio is 150 to 300, and the liquid hourly volume space velocity is 0.2h -1 ~0.8h -1 Under the optimal conditions, the conversion rate of 3-hydroxypropionate can reach 99.3%, and the selectivity of 1,3-propylene glycol is 98.2%. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with the embodiments, but the present invention is not limited by these embodiments.
[0032] The instrument used for gas chromatography testing in the present invention is Clarus 680 from PerkinElmer;
[0033] The sodium ion analyzer in the present invention was purchased from Beijing Times Xinwei Measurement and Control Equipment Co., Ltd., model TP330;
[0034] The fixed bed reactor in the present invention was purchased from Qisi Technology (Tianjin) Co., Ltd., wherein the inner diameter of the reaction tube was 8 mm;
[0035] The fullerene C60 in the present invention was purchased from Anaiji Chemical Co., Ltd. with a purity of 95%;
[0036] The fullerene C70 in the present invention was purchased from Anaiji Chemical Co., Ltd. with a purity of 99%;
[0037] In the present invention, M salts (Zn(NO3)2·6H2O, purity 99%, Cr(NO3)3·9H2O, purity 98%, Mn(NO3)2·4H2O, purity 98%, Ti(NO3)4, purity 99%, La(NO3)3·6H2O, purity 99%) and copper salt (Cu(NO3)2·3H2O, purity 99%) were purchased from Sinopharm Group;
[0038] The silica sol solution in the present invention is purchased from Yutu Chemical Industry, and the mass fraction concentration is 30%.
[0039] Example 1
[0040] This embodiment provides a catalyst, and the preparation method is as follows:
[0041] 2.0 g of fullerene C60, 15.0 g of Cu(NO3)2·3H2O and 4.5 g of Zn(NO3)2·6H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 45.0 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C60 0.1 Zn 0.05 Cu 0.2 / (SiO2) 0.65 .
[0042] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0043] Example 2
[0044] This embodiment provides a catalyst, and the preparation method is as follows:
[0045] 2.0 g of fullerene C70, 15.0 g of Cu(NO3)2·3H2O and 4.5 g of Zn(NO3)2·6H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 45.0 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C70 0.1 Zn 0.05 Cu 0.2 / (SiO2) 0.65 .
[0046] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0047] Example 3
[0048] This embodiment provides a catalyst, and the preparation method is as follows:
[0049] 2.0 g of fullerene C60, 15.0 g of Cu(NO3)2·3H2O and 7.7 g of Cr(NO3)3·9H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 45.0 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na. + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C60 0.1 Cr0.05 Cu 0.2 / (SiO2) 0.65 .
[0050] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0051] Example 4
[0052] This embodiment provides a catalyst, and the preparation method is as follows:
[0053] 2.0 g of fullerene C60, 15.0 g of Cu(NO3)2·3H2O and 4.6 g of Mn(NO3)2·4H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 45.0 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C60 0.1 Mn 0.05 Cu 0.2 / (SiO2) 0.65 .
[0054] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0055] Example 5
[0056] This embodiment provides a catalyst, and the preparation method is as follows:
[0057] 2.0 g of fullerene C60, 15.0 g of Cu(NO3)2·3H2O and 6.2 g of Ti(NO3)4 were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 45.0 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C60 0.1 Ti 0.05 Cu 0.2 / (SiO2) 0.65 .
[0058] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0059] Example 6
[0060] This embodiment provides a catalyst, and the preparation method is as follows:
[0061] 2.0 g of fullerene C60, 10.1 g of Cu(NO3)2·3H2O and 3.1 g of Zn(NO3)2·6H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 27.0 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na +and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C60 0.15 Zn 0.05 Cu 0.2 / (SiO2) 0.6 .
[0062] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0063] Example 7
[0064] This embodiment provides a catalyst, and the preparation method is as follows:
[0065] 2.0 g of fullerene C60, 7.6 g of Cu(NO3)2·3H2O and 2.3 g of Zn(NO3)2·6H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 18.3 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C60 0.2 Zn 0.05 Cu 0.2 / (SiO2) 0.55 .
[0066] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0067] Example 8
[0068] This embodiment provides a catalyst, and the preparation method is as follows:
[0069] 2.0 g of fullerene C60, 7.6 g of Cu(NO3)2·3H2O and 9.2 g of Zn(NO3)2·6H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 47.0 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C60 0.1 Zn 0.1 Cu 0.1 / (SiO2) 0.7 .
[0070] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0071] Example 9
[0072] This embodiment provides a catalyst, and the preparation method is as follows:
[0073] 2.0 g of fullerene C60, 15.1 g of Cu(NO3)2·3H2O, 3.1 g of Cr(NO3)3·9H2O and 1.8 g of Zn(NO3)2·6H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 44.0 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na. + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is calculated based on the amount of metal ions added and the amount of metal ions washed away.
[0074] C60 0.1 Cr 0.02 Zn 0.02 Cu 0.2 / (SiO2) 0.66 .
[0075] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0076] Example 10
[0077] This embodiment provides a catalyst, and the preparation method is as follows:
[0078] Weigh 2.0 g of fullerene C60, 15.1 g of Cu(NO3)2·3H2O, 3.1 g of Cr(NO3)3·9H2O and 3.0 g of Mn(NO3)2·4H2O, dissolve them in 200 mL of distilled water and stir them ultrasonically. Then, add 43.3 g of silica sol solution under stirring and stir to mix them. Then, add 30 g of ammonia water at room temperature, heat to 90 °C and age for 12 h. Filter and collect the precipitate, wash it thoroughly with deionized water, and use a sodium ion analyzer to ensure that the washing solution no longer contains Na +and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is calculated based on the amount of metal ions added and the amount of metal ions washed away.
[0079] C60 0.1 Cr 0.02 Mn 0.03 Cu 0.2 / (SiO2) 0.65 .
[0080] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0081] Embodiment 11
[0082] This embodiment provides a catalyst, and the preparation method is as follows:
[0083] 2.0 g of fullerene C60, 15.1 g of Cu(NO3)2·3H2O, 1.8 g of Mn(NO3)2·4H2O and 3.1 g of Zn(NO3)2·6H2O were weighed and dissolved in 200 mL of distilled water and ultrasonically stirred. Then, 43.3 g of silica sol solution was added under stirring and stirred to mix well. Then, 30 g of ammonia water was added at room temperature and heated to 90 °C for aging for 12 h. The precipitate was collected by filtration and washed thoroughly with deionized water. A sodium ion analyzer was used to ensure that the washing solution no longer contained Na. + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is
[0084] C60 0.1 Mn 0.02 Zn 0.03 Cu 0.2 / (SiO2) 0.65 .
[0085] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0086] Example 12
[0087] This embodiment provides a catalyst, and the preparation method is as follows:
[0088] Weigh 2.0 g of fullerene C60, 15.1 g of Cu(NO3)2·3H2O, 1.8 g of Mn(NO3)2·4H2O, 1.2 g of La(NO3)3·6H2O and 1.8 g of Zn(NO3)2·6H2O, dissolve them in 200 mL of distilled water and stir them ultrasonically, then add 42.7 g of silica sol solution under stirring and stir to mix them well; then add 30 g of ammonia water at room temperature, heat to 90 ° C and age for 12 h, collect the precipitate by filtration, wash it thoroughly with deionized water, and use a sodium ion analyzer to ensure that the washing liquid no longer contains Na + and other metal ions, drying the precipitate at 120°C for 12 hours, and then calcining it at 400°C for 6 hours to obtain a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst is C60 0.1 Zn 0.02 Mn 0.02 La 0.02 Cu 0.2 / (SiO2) 0.64 .
[0089] The above-obtained fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was granulated into a 40-mesh size, 3.0 g was weighed, and loaded into the middle of a reaction tube of a fixed-bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed-bed reactor were filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min was introduced, and the temperature was raised from room temperature to 40°C within a set time of 30 minutes; then the temperature was raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0090] Comparative Example 1
[0091] This comparative example provides a catalyst, and the preparation method is as follows:
[0092] Weigh 15.0g Cu(NO3)2·3H2O and 4.5g Zn(NO3)2·6H2O, dissolve in 200mL distilled water and stir ultrasonically, then add 45.0g silica sol solution under stirring, stir to mix; then add 30g ammonia water at room temperature, heat to 90℃ and age for 12h, filter and collect the precipitate, wash thoroughly with deionized water, and use a sodium ion analyzer to ensure that the washing solution no longer contains Na + and other metal ions, the precipitate was dried at 120°C for 12 hours, and then calcined at 400°C for 6 hours to obtain an unmodified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions input and the amount of metal ions washed away, the structural formula of the unmodified copper-containing mixed metal silicon-oxygen catalyst was Zn 0.06 Cu 0.22 / (SiO2) 0.72 .
[0093] The unmodified copper-containing mixed metal silicon oxygen catalyst obtained above is granulated into a 40 mesh size, 3.0 g is weighed, and loaded into the middle of the reaction tube of the fixed bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed bed reactor are filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min is introduced, and the temperature is raised from room temperature to 40°C within a set time of 30 minutes; then the temperature is raised to 400°C within 300 minutes, reduced at this temperature for 280 minutes, and then lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0094] Comparative Example 2
[0095] This comparative example provides a catalyst, and the preparation method is as follows:
[0096] Weigh 15.0g Cu(NO3)2·3H2O and 7.7g Cr(NO3)3·9H2O, dissolve in 200mL distilled water and stir ultrasonically, then add 45.0g silica sol solution under stirring, stir to mix; then add 30g ammonia water at room temperature, heat to 90℃ and age for 12h, collect the precipitate by filtration, wash thoroughly with deionized water, and use a sodium ion analyzer to ensure that the washing solution no longer contains Na + and other metal ions, the precipitate was dried at 120°C for 12 hours, and then calcined at 400°C for 6 hours to obtain an unmodified copper-containing mixed metal silicon-oxygen catalyst; according to the amount of metal ions added and the amount of metal ions washed away, the structural formula of the unmodified copper-containing mixed metal silicon-oxygen catalyst is Cr 0.06 Cu 0.22 / (SiO2) 0.72 .
[0097] The unmodified copper-containing mixed metal silicon oxygen catalyst obtained above is granulated into a 40 mesh size, 3.0 g is weighed, and loaded into the middle of the reaction tube of the fixed bed reactor, and the spaces at the front and rear ends of the reaction tube of the fixed bed reactor are filled with inert quartz sand; a H2 (5% vol) / N2 mixed reducing gas with a flow rate of 90 mL / min is introduced, and the temperature is raised from room temperature to 40°C within a set time of 30 minutes; then the temperature is raised to 400°C within 300 minutes, and reduced at this temperature for 280 minutes, and then the temperature is lowered to 160°C in a reducing gas atmosphere to obtain the catalyst.
[0098] In order to further illustrate the advancement of the copper-containing mixed metal silicon-oxygen catalyst modified with fullerene prepared by the present invention, the following tests are performed;
[0099] Test Example 1-14
[0100] The copper-containing mixed metal silicon-oxygen catalyst C60 modified with fullerene prepared in Examples 1-12 was used respectively. 0.1 Zn 0.05 Cu 0.2 / (SiO2) 0.65 、C70 0.1 Zn 0.05 Cu 0.2 / (SiO2) 0.65 、C60 0.1 Cr 0.05 Cu 0.2 / (SiO2) 0.65 、C60 0.1 Mn 0.05 Cu 0.2 / (SiO2) 0.65 、C60 0.1 Ti 0.05 Cu 0.2 / (SiO2) 0.65 、C60 0.15 Zn 0.05 Cu 0.2 / (SiO2) 0.6 、C60 0.2 Zn 0.05 Cu 0.2 / (SiO2) 0.55 、C60 0.1 Zn 0.1 Cu 0.1 / (SiO2) 0.7 、C60 0.1 Cr 0.02 Zn 0.02 Cu 0.2 / (SiO2)0.66 、C60 0.1 Cr 0.02 Mn 0.03 Cu 0.2 / (SiO2) 0.65 、C60 0.1 Mn 0.02 Zn 0.03 Cu 0.2 / (SiO2) 0.65 、C60 0.1 Zn 0.02 Mn 0.02 La 0.02 Cu 0.2 / (SiO2) 0.64 And the unmodified copper-containing mixed metal silicon-oxygen catalyst Zn prepared in Comparative Example 1-2 0.06 Cu 0.22 / (SiO2) 0.72 and Cr 0.06 Cu 0.22 / (SiO2) 0.72 The catalytic reaction performance of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was verified by catalyzing the preparation of 1,3-propylene glycol from methyl 3-hydroxypropionate.
[0101] The catalyst loading was 3.0 g, the solvent was methanol, the reaction temperature was 160 ° C, the reaction pressure was 1 atm, the H2 flow rate was 40 mL / min and the 3-hydroxypropionic acid methyl ester flow rate was 0.1 mL / min, the liquid hourly volume space velocity was 0.3 h -1 The reaction was carried out for 120 hours under the conditions of , wherein the molar ratio of methyl 3-hydroxypropionate to hydrogen was 1:100, and the volume ratio of 3-hydroxypropionate to solvent was 1:8; the results are recorded in the following Table 1.
[0102] Table 1 Summary of reaction results
[0103]
[0104] In Table 1, the calculation formulas for the conversion rate of 3-hydroxypropionate and the selectivity of 1,3-propylene glycol are as follows:
[0105] 3-hydroxypropionic acid methyl ester conversion rate = (amount of 3-hydroxypropionic acid methyl ester - unreacted amount) / amount of 3-hydroxypropionic acid methyl ester * 100%;
[0106] 1,3-propanediol selectivity = amount of 1,3-propanediol produced / amount of all products produced*100%.
[0107] It can be seen from the data in Table 1 above that the catalytic performance of the fullerene-modified copper-containing mixed metal silicon-oxygen catalysts prepared in Examples 1-12 of the present invention is significantly higher than that of the catalysts prepared in Comparative Examples 1 and 2, and it is not difficult to find that the fullerene-modified copper-containing mixed metal silicon-oxygen catalysts prepared in Examples 6 and 7 of the present invention have the best catalytic performance, and the conversion rate of methyl 3-hydroxypropionate and the selectivity of 1,3-propylene glycol are significantly better than those of other examples.
[0108] Test Example 15-58
[0109] Example 6 was used to prepare a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst C60 0.15 Zn 0.05 Cu 0.2 / (SiO2) 0.6 The catalytic reaction performance of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was verified by catalyzing the preparation of 1,3-propylene glycol from methyl 3-hydroxypropionate.
[0110] In order to fully understand the reaction performance of the catalyst, the C60 0.15 Zn 0.05 Cu 0.2 / (SiO2) 0.6 In the process of catalyzing methyl 3-hydroxypropionate (3-HMP) to prepare 1,3-propylene glycol, the loading amount of the catalyst is 3.0 g, the molar ratio of the 3-hydroxypropionate to hydrogen is 1:100, and the volume ratio of the 3-hydroxypropionate to the solvent is 1:8;
[0111] (1) While keeping the solvent as methanol, the reaction pressure as 1 atm, the H2 flow rate as 40 mL / min, and the 3-HMP flow rate as 0.1 mL / min, the reaction temperature was changed, and the conversion rate of methyl 3-hydroxypropionate and the selectivity of 1,3-propylene glycol were recorded at reaction temperatures of 120°C, 130°C, 140°C, 150°C, 155°C, 165°C, 170°C, 180°C, 190°C, 200°C, and 210°C, respectively;
[0112] (2) While keeping the solvent as methanol, the reaction temperature at 160°C, the H2 flow rate at 40 mL / min, and the 3-HMP flow rate at 0.1 mL / min, the reaction pressure was changed, and the conversion rate of methyl 3-hydroxypropionate and the selectivity of 1,3-propylene glycol were recorded under the reaction pressures of 2 atm, 4 atm, 6 atm, 8 atm, 10 atm, 20 atm, 30 atm, 40 atm, and 50 atm, respectively;
[0113] (3) While keeping the solvent as methanol, the reaction temperature at 160°C, the reaction pressure at 1 atm, and the 3-HMP flow rate at 0.1 mL / min, change the H2 flow rate and record the conversion rate of methyl 3-hydroxypropionate and the selectivity of 1,3-propylene glycol when the H2 flow rate is 30 mL / min, 35 mL / min, 45 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min, and 100 mL / min, respectively;
[0114] (4) While keeping the solvent as methanol, the reaction temperature at 160°C, the reaction pressure at 1 atm, and the H2 flow rate at 40 mL / min, the 3-HMP flow rate was changed, and the conversion rate of methyl 3-hydroxypropionate and the selectivity of 1,3-propylene glycol were recorded when the 3-HMP flow rate was 0.02 mL / min, 0.04 mL / min, 0.06 mL / min, 0.08 mL / min, 0.12 mL / min, 0.14 mL / min, 0.16 mL / min, 0.18 mL / min, and 0.20 mL / min, respectively;
[0115] (5) While maintaining the reaction pressure at 1 atm, the reaction temperature at 160°C, the H2 flow rate at 40 mL / min, and the 3-HMP flow rate at 0.1 mL / min, the solvent was changed and the conversion rate of methyl 3-hydroxypropionate and the selectivity of 1,3-propylene glycol were recorded when the solvent was pentane, benzene, toluene, hexane, and tetrahydrofuran, respectively. The results are shown in Table 2.
[0116] Table 2 Summary of reaction results
[0117]
[0118] Test Example 15-57
[0119] Example 6 was used to prepare a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst C60 0.15 Zn 0.05 Cu 0.2 / (SiO2) 0.6 The catalytic reaction performance of the fullerene-modified copper-containing mixed metal silicon-oxygen catalyst was verified by catalyzing the preparation of 1,3-propylene glycol from methyl 3-hydroxypropionate.
[0120] In order to fully understand the reaction performance of the catalyst, the C60 0.15 Zn 0.05 Cu 0.2 / (SiO2) 0.6In the process of catalyzing 3-hydroxypropionic acid ester to prepare 1,3-propylene glycol, the loading amount of the catalyst is 3.0 g, the molar ratio of the 3-hydroxypropionic acid ester to hydrogen is 1:100, and the volume ratio of the 3-hydroxypropionic acid ester to the solvent is 1:8; under the conditions of methanol as the solvent, 160°C as the reaction temperature, 1 atm as the reaction pressure, 40 mL / min as the H2 flow rate, and 0.1 mL / min as the 3-hydroxypropionic acid ester flow rate, the type of 3-hydroxypropionic acid ester is changed, and the conversion rate of 3-hydroxypropionic acid ester and the selectivity of 1,3-propylene glycol are recorded when the 3-hydroxypropionic acid ester is ethyl 3-hydroxypropionic acid, n-propyl 3-hydroxypropionic acid, isopropyl 3-hydroxypropionic acid, n-butyl 3-hydroxypropionic acid, isobutyl 3-hydroxypropionic acid, tert-butyl 3-hydroxypropionic acid, and n-pentyl 3-hydroxypropionic acid, respectively. The results are recorded in Table 3.
[0121] Table 3 Summary of reaction results
[0122]
[0123] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A fullerene-modified copper-containing mixed metal silicon-oxygen catalyst, characterized in that: The general formula of the catalyst is C' x M y Cu z / (SiO2) m ; wherein C' is selected from fullerene; M is selected from at least one of transition metal elements and / or lanthanide metal elements; 0.05≤x≤0.39, 0.01≤y≤0.20, 0.20≤z≤0.50, 0.40≤m≤0.74, and x+y+z+m=1.
2. The catalyst according to claim 1, characterized in that The M is selected from any one, any two, or any three of zinc, manganese, zirconium, titanium, chromium, cobalt, silver, gold, lanthanum, cerium, praseodymium, and europium; And / or, the fullerene is selected from C60 or C70.
3. A method for preparing a fullerene-modified copper-containing mixed metal silicon-oxygen catalyst, characterized in that: The following steps are involved: Fullerene, copper salt, M salt and carrier are mixed, and then an alkaline precipitant is added to react to obtain a precursor, which is calcined in an inert atmosphere.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the fullerene, copper salt, M salt, carrier and alkaline precipitant is 2.0:(5-20):(1-15):(15-50):(1-50), preferably 2.0:(7.6-15.1):(2.3-9.2):(18.3-47):30; And / or, the alkaline precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, urea, ammonia water, ammonium carbonate, ammonium bicarbonate, sodium methoxide, sodium ethoxide, sodium n-propoxide, potassium methoxide, potassium ethoxide, potassium n-propoxide, potassium isopropoxide, potassium n-butoxide, potassium isobutoxide, potassium tert-butoxide, sodium amide, and potassium amide; And / or, the preparation method further comprises: drying the precursor before calcining; preferably, the drying temperature is 50°C to 150°C, more preferably 90°C to 120°C, and the drying time is 6 hours to 15 hours, more preferably 10 hours to 12 hours; And / or, the calcination temperature is 200°C to 600°C, preferably 300°C to 400°C, and the calcination time is 2 hours to 8 hours, preferably 4 hours to 6 hours; And / or, the inert atmosphere is nitrogen.
5. The preparation method according to claim 3 or 4, characterized in that: The copper salt is selected from at least one of copper sulfate, copper nitrate, cuprous sulfate, organic acid copper, copper halide, cuprous halide, cuprous nitrate, and organic acid cuprous; And / or, the fullerene is selected from C60 or C70; And / or, the M salt is at least one selected from the group consisting of M acetate, M sulfate, and M nitrate; And / or, the carrier is a silica sol solution, and the mass fraction concentration of the silica sol solution is 5% to 40%, preferably 10% to 30%.
6. The preparation method according to claim 4, characterized in that: The preparation method further comprises: a step of heating and aging the precursor before drying, preferably, the heating temperature is 50°C to 100°C, and the aging time is 4h to 16h; further preferably, the heating temperature is 60°C to 90°C, and the aging time is 8h to 12h; and / or, the preparation method further comprises: a step of filtering and collecting the precipitate after heating and aging, and washing the precipitate with deionized water; And / or, the preparation method further includes: a reduction step after the precursor is calcined; preferably, the reduction is carried out using a reducing gas, and the flow rate of the reducing gas is 90 mL / min; more preferably, the reducing gas is hydrogen or a mixture of hydrogen and nitrogen; further preferably, the reduction temperature is 250°C to 500°C, and further preferably 250°C to 450°C, and the reduction time is 3 hours to 8 hours, and further preferably 4 hours to 5 hours.
7. A method for preparing 1,3-propylene glycol, characterized in that: In the presence of a catalyst, 3-hydroxypropionic acid ester is contacted with hydrogen to react to prepare 1,3-propylene glycol; wherein the catalyst is the catalyst described in claim 1 or 2 above or a catalyst prepared by the preparation method described in any one of claims 3-6.
8. The method according to claim 7, characterized in that The molar ratio of the 3-hydroxypropionic acid ester to hydrogen is 1:(100-1000); And / or, the 3-hydroxypropionic acid ester is selected from one of methyl 3-hydroxypropionate, ethyl 3-hydroxypropionate, propyl 3-hydroxypropionate, butyl 3-hydroxypropionate and pentyl 3-hydroxypropionate; And / or, the contact reaction is carried out in the presence of a solvent; preferably, the volume ratio of the 3-hydroxypropionic acid ester to the solvent is 1:(8-10); and / or, the solvent is selected from any one of alcohol, ether, saturated alkane, and saturated aromatic hydrocarbon, more preferably, the alcohol is selected from any one of methanol, ethanol, propanol, and butanol, the ether is selected from any one of diethyl ether, methyl tert-butyl ether, and tetrahydrofuran, and the saturated alkane is selected from any one of hexane, heptane, and octane; And / or, the contact reaction conditions include: reaction temperature of 80°C to 220°C, preferably 100°C to 180°C; reaction pressure of 1atm to 40atm, preferably 1atm to 10atm; reaction time of 0.1 hour to 500 hours; liquid hourly volume space velocity of 0.02h -1 ~1.0h -1 , preferably 0.2h -1 ~0.8h -1 .
Citation Information
Patent Citations
Prepn process of 3-hydroxy propionate and propylene glycol
CN101020635A
Method for preparing 1,3-propylene glycol with ethylene oxide coupling synthesis gas
CN110105169A
Method for preparation of 1,3-alkamediol by 3-carboxy ester
CN1355160A
Glycol production
US3463819A
Process for preparing 1,3-propanediol from methyl 3-hydroxypropionate
US6191321B1